Acute Enteric Eosinophilic Myenteric Ganglionitis: A challenging and uncommon case of lung adenocarcinoma - Deniz Esin Tekcan Şanlı; Emel Ozveri; Ahmet Necati Sanli; Serpil Yilmaz; Metin Ertem; Safak Kiziltas (Medicine Science, 2022)
Chronic intestinal pseudo-obstruction (CIPO) is caused by metabolic and endocrine factors, but it can also be caused by the cancer's paraneoplastic effect. The cancers most associated with paraneoplastic syndromes are lung cancers and are generally associated with small cell lung cancers. Lung adenocarcinomas may rarely cause paraneoplastic syndromes, however, they mostly cause general effects such as cachexia and leukocytosis. The goal of this case report was to provide a case of non-mechanical obstruction due to lung adenocarcinoma as a very unusual cause of intestinal pseudo-obstruction, together with clinical, laboratory, and imaging results. [Med-Science 2022; 11(1.000): 410-2]